2020
DOI: 10.1186/s13014-020-01561-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neoadjuvant radiotherapy on survival of non-metastatic pancreatic ductal adenocarcinoma: a SEER database analysis

Abstract: Background: Neoadjuvant radiotherapy has been shown to improve marginal negative resection and local control of Pancreatic Ductal Adenocarcinoma (PDAC). However, whether it improves overall survival (OS) in patients with non-metastatic PDAC remains controversial. Therefore, the purpose of this study was to analyze the benefits of only surgery, neoadjuvant radiotherapy, adjuvant radiotherapy, and surgery plus chemotherapy for OS in patients with non-metastatic PDAC. Methods: PDAC diagnosed by surgical histopath… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Not only for GEA but also for pancreatic cancer, the question whether neoadjuvant therapy should be used in early-stage patients has always been a question. The reason for opposing neoadjuvant therapy for patients with early resectable cancer is that neoadjuvant therapy may cause patients to miss the best opportunity for surgery, making lesions that could be resectable at R0 progress to incurable resection, or even distant metastases [ 29 , 30 ]. Our consequences are confirmed by other retrospective researches, indicating that routine use of neoadjuvant induction therapy may be adverse rather than beneficial to survival in all T1-2N0M0 patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only for GEA but also for pancreatic cancer, the question whether neoadjuvant therapy should be used in early-stage patients has always been a question. The reason for opposing neoadjuvant therapy for patients with early resectable cancer is that neoadjuvant therapy may cause patients to miss the best opportunity for surgery, making lesions that could be resectable at R0 progress to incurable resection, or even distant metastases [ 29 , 30 ]. Our consequences are confirmed by other retrospective researches, indicating that routine use of neoadjuvant induction therapy may be adverse rather than beneficial to survival in all T1-2N0M0 patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant therapy corresponds to a treatment used for borderline and locally advanced lesions that consists of the combination of chemotherapy and radiotherapy 7 . The benefits of such a procedure include decreasing the likelihood of metastatic disease and tumor shrinkage to optimize surgical resection, as well as being associated with a greater survival advantage even in early-stage pancreatic adenocarcinoma 10 , 12 . However, some evidence has not demonstrated benefits associated with this procedure in the management of pancreatic cancer and, in addition, has suggested that it may be harmful to treatment and therefore is not a recommended treatment in all oncology guidelines 13 .…”
Section: Adjuvant Treatmentmentioning
confidence: 99%
“…It works by delivering ionizing radiation directly to the primary tumor and regional lymph nodes, which may cause genetic damage and ultimately apoptosis of cancer cells (6). However, our previous study has shown that RT does not benefit the survival of PDAC patients with stage T1-3N0M0 (7). For surgically resected PDAC patients, the NCCN and American Society for Radiation Oncology (ASTRO) also recommend conventional aRT for only a subset of high-risk patients (including positive lymph nodes (stage IIB/III) and margins) (5,8).…”
Section: Introductionmentioning
confidence: 99%